Direct cost of maintenance of totally implanted central venous catheter patency (Revista Latino-Americana de Enfermagem, 2018)
Objective: to identify the average direct cost of maintaining the patency of totally implanted central venous catheter with heparin at a Day Hospital of a public hospital of high complexity specialized in the treatment of cancer patients, and estimate the average direct cost of replacing heparin with sodium chloride 0.9%. Method: quantitative, exploratory-descriptive study, with a sample of 200 non-participant observations of the maintenance of totally implanted central venous catheters with heparin. The average direct cost was calculated by multiplying the (clocked) time spent by professionals to complete the procedure by the direct unit cost of workforce, added to the cost of materials and solutions. Results: the estimated total direct cost of catheter maintenance with heparin was US$ 9.71 (SD=1.35) on average, ranging from US$ 7.98 to US$ 23.28. The estimated total direct cost of maintenance with 0.9% sodium chloride in the place of heparin was US$ 8.81 (SD=1.29) on average, resulting in a reduction of US$ 0.90 per procedure. Conclusion: the results contributed to propose strategies to assist in cost containment/minimization in this procedure. The replacement of heparin by 0.9% sodium chloride proved to be an option to reduce the total average direct cost.